the role of the NTT Provincial Border Management Agency in Resolving Land Boundary issues between Indonesia and Timor-Leste (Case study in North Netemnanu Village) - Elisabeth NSB Tukan; Roy Adrian Dimoe (Goodwood Publishing, 2024)
Purpose: To identify and study the causes and efforts to resolve border disputes in the territory of Naktuka Amfoang East, Indonesia and the Oecusian Territory of Timor-Leste. Research methodology: This research is empirical legal research, namely research conducted by examining secondary data initially and then continuing with research on primary data in the field or on the community. Results: (1) the role of the Border Management Agency is very important in maintaining security and order in the border area, as well as facilitating cross-border trade and activities. (2) The Border Management Agency also has a role in maintaining state sovereignty, preventing the entry of illegal goods, and monitoring the movements of people entering and leaving the border area. Limitations: The researchers experienced difficulties in obtaining data from the NTT Regional Border Management Agency, because the staff claimed not to have any data, therefore the analysis of the role of BPP was based solely on normative provisions. Contribution: (1) This research is expected to provide a contribution or contribution of thought to the Border Management Agency of NTT Province, the Ministry of Home Affairs of the Government of the NTT Provincial Region in determining the border point of land in Naktuka. (2) The results of this research are expected to be used as a reference for academics who want to do research related to the same thing.